Time‐series observations of photosynthetic oxygen production in the subtropical western North Pacific by an underwater profiling buoy system. (12th November 2019) - Fujiki, Tetsuichi; Inoue, Ryuichiro; Honda, Makio C.; Wakita, Masahide; Mino, Yoshihisa; Sukigara, Chiho; Abe, Osamu
Abstract: We conducted time‐series observations in the northwestern part of the North Pacific subtropical gyre (30°N, 145°E) from July 2012 to March 2013 using a profiling buoy system equipped with a fast repetition rate fluorometer and dissolved oxygen (DO) sensor in order to understand vertical and temporal variations in gross oxygen production (GOP) by phytoplankton and its contribution to the oxygen cycle in the upper ocean. Under stratified conditions (July–November), daily GOP slightly exceeded 2 mmol O2 m −3 d −1 and only in near‐surface waters. However, during periods of vertical mixing (December–March) when phytoplankton blooms occurred, daily GOP increased in the upper 30 m and often exceeded 5 mmol O2 m −3 d −1 . The depth‐integrated daily GOP within the euphotic layer (∫GOPEL ) was relatively low (84.0 ± 23.6 mmol O2 m −2 d −1 ) during stratification, but increased gradually with vertical mixing and reached 460 mmol O2 m −2 d −1 on 17 March 2013. Additionally, during stratified conditions, a subsurface oxygen maximum (SOM) formed below the mixed‐layer depth (MLD) because the steep density gradient constrained upward diffusion of oxygen produced below the MLD. During the period of vertical mixing, the SOM disappeared, and DO concentrations within the upper 100 m increased through both increasing ∫GOPEL and atmospheric oxygen uptake. Using our buoy observations and air–sea gas flux model, we estimated that 24% ± 7% of ∫GOPEL was emitted to the atmosphere during the stratification period, and ∫GOPEL during the mixing period was about 2.4 times the rate of oxygen uptake by the ocean from the atmosphere.